PERANCANGAN PLTS GROUND MOUNTED DI AREA PARKIR SELATAN PUSAT PEMERINTAHAN KABUPATEN BADUNG - Kerans, M. F. A. S.; Giriantari, I. A. D.; Santiari, D. A. S.; Ariastina, W. G.; Setiawan, I N.; Kumara, I N. S. (Jurnal SPEKTRUM, 2025)
The increasing consumption of fossil-based electricity has led to higher carbon emissions and accelerated global climate change. To address this issue, the Indonesian government has set a target of 23% renewable energy share by 2025, as stated in the PLN Electricity Supply Business Plan (RUPTL) 2021–2030. Badung Regency has high solar energy potential; therefore, this study aims to design and analyze the performance of an on-grid Solar Power Plant located in the southern parking area of the Badung Regency Government Center to support clean energy policies. The utilization of the parking area was chosen to optimize land use efficiency. The PV system employs 592 solar panels with a capacity of 575 Wp each, resulting in a total installed capacity of 340.3 kWp and an annual energy output of 540,889.90 kWh. On weekdays, the entire energy produced is utilized, supplying approximately 72% of the daily energy demand of 2,053.24 kWh, while the remaining demand is met by PLN through an on-grid system. On weekends or holidays, energy demand decreases to 326.18 kWh per day. The total annual energy utilization from the PV system amounts to 212,910.42 kWh.